A heat-powered ejector chiller working with low-GWP fluid R1233zd(E) (Part 1: Experimental results). (January 2021) - Mahmoudian, Jafar; Rocchetti, Andrea; Mazzelli, Federico; Milazzo, Adriano
Abstract: A prototype ejector chiller with nominal cooling power of 40 kW, designed according to the "CRMC" criterion, has been tested by our research group since 2011. The prototype has undergone several refinements and finally has been upgraded to R1233zd(E), which is non-flammable, has low-GWP and favourable thermodynamic properties, i.e. "dry-expansion" and moderate pressure at generator. In terms of saturation pressure curve, the new fluid is similar to R245fa, which was previously used in the prototype. Hence, R1233zd(E) has been basically used as a "drop-in" replacement. The ejector chiller was tested at different evaporation temperatures (2.5 to 10°C), typical of air conditioning applications. Saturation temperatures at generator from 95 to 105°C have been selected as representative of waste-heat recovery. The experimental findings prove that the CRMC ejector has a satisfactory performance with the new working fluid.